2020
DOI: 10.1073/pnas.2003090117
|View full text |Cite
|
Sign up to set email alerts
|

The Great Oxidation Event preceded a Paleoproterozoic “snowball Earth”

Abstract: The inability to resolve the exact temporal relationship between two pivotal events in Earth history, the Paleoproterozoic Great Oxidation Event (GOE) and the first “snowball Earth” global glaciation, has precluded assessing causality between changing atmospheric composition and ancient climate change. Here we present temporally resolved quadruple sulfur isotope measurements (δ34S, ∆33S, and ∆36S) from the Paleoproterozoic Seidorechka and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(76 citation statements)
references
References 55 publications
0
64
0
Order By: Relevance
“…Unlike other elements with complex redox chemistry, such as Fe or S, Li has straightforward redox chemistry and relatively smaller associated networks. We emphasize that dragon is designed to analyze complex and larger mineral-chemistry networks with complex redox changes, as associated with oxygenation events for example (Scott et al, 2008;Och and Shields-Zhou, 2012;Sahoo et al, 2012;Warke et al, 2020), but we focus on the simpler Li network here to clearly showcase dragon's functionality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike other elements with complex redox chemistry, such as Fe or S, Li has straightforward redox chemistry and relatively smaller associated networks. We emphasize that dragon is designed to analyze complex and larger mineral-chemistry networks with complex redox changes, as associated with oxygenation events for example (Scott et al, 2008;Och and Shields-Zhou, 2012;Sahoo et al, 2012;Warke et al, 2020), but we focus on the simpler Li network here to clearly showcase dragon's functionality.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, dragon's fourth tab "Mineral formation timeline" provides a chronological view of mineral formation scaffolded along geologic eras, including periods of tectonic assembly, oxygenation events in Earth's history (Farquhar et al, 2000;Scott et al, 2008;Och and Shields-Zhou, 2012;Sahoo et al, 2012;Luo et al, 2016;Warke et al, 2020), and early geochemical evidence for microbial metabolisms (Moore et al, 2017) ( Figure 1D).…”
Section: Analyzing Network In Dragonmentioning
confidence: 99%
“…However, it is currently unclear whether this was a globally synchronous event with estimates for MIF-S disappearance varying from 2.45 to 2.32 Ga due to uncertainties over memory effects caused by oxidative weathering of sulphides and recycling of the MIF signature (Reinhard et al, 2013;Philippot et al, 2018;cf. Torres et al, 2018;Warke et al, 2020b). The MIF-S record has also shown structure within the later Archean that could potentially be used as a future stratigraphic marker (Farquhar et al, 2007;Domagal-Goldman et al, 2008;Halevy et al, 2010;Kurzweil et al, 2013) if the structure is confirmed as a global phenomenon rather than superimposed local signals (see e.g.…”
Section: Archean Eon (C 40 To 245/25 Ga)mentioning
confidence: 99%
“…Although the GOE is sometimes taken to refer to a more prolonged interval of the early Paleoproterozoic, we restrict our usage here to this shorter interval between c. 2.45 to c. 2.32 Ga, with a preference for the earlier age (e.g. Warke et al, 2020b). The GOE has been defined in various ways but in recent years has been presumed to begin when atmospheric oxygen had accumulated sufficiently to prevent the formation and/or preservation of mass independent S-isotope fractionation in sedimentary rocks (Farquhar et al, 2000;Bekker et al, 2004).…”
Section: Archean Eon (C 40 To 245/25 Ga)mentioning
confidence: 99%
“…Accordingly, the Calvin cycle is also named the reductive pentose phosphate cycle. Rubisco evolved from a methionine salvage enzyme [ 12 ] over 2.9 billion years ago [ 13 ], before the great oxygenation event [ 14 ]. Research has explored Rubisco evolution [ 15 19 ] and biochemistry [ 20 23 ], identifying several forms [ 24 26 ].…”
Section: Introductionmentioning
confidence: 99%